Layanan Informasi Karier Berbasis Field Trip untuk Meningkatkan Pemahaman Karier Siswa - Hijrah Eko Putro; Muhammad Japar (Universitas Mathla'ul Anwar Banten, 2019)
CAREER INFORMATION SERVICES BASED ON FIELD TRIP TO IMPROVE STUDENTS UNDERSTANDING. The aims of this study is to: (1) find out the implementation of career information services in Magelang Regency; (2) produce career information service models with field trip techniques to improve career understanding of vocational students; (3) determine the level of career understanding of students in Muhammadiyah 1 Mertoyudan Vocational School; and (4) knowing the effectiveness of career information services with field trip techniques to improve career understanding of students at Mertoyudan 1 Muhammadiyah Vocational School. The population in this study were students of class XII of Muhammadiyah 1 Mertoyudan Vocational School with 29 students who were used as samples. The study design used pre-experimental: one group pretest-posttest design with saturated sampling. The data analysis technique used is Paired sample t-Test with consideration in this study using one independent variable (Independent Variable). The result of the effectiveness test of this study is that there is an increase in students' career understanding through career information services with field trip techniques. The level of career understanding of students has increased after participating in career information services with field trip techniques. This is seen from the increase in the results of the student's career understanding scale before and after being given career information services with a field trip technique of 28% and strengthened through the effectiveness test using a t-test that shows the -t count <-t-table, which is -9,583 <-2,045 or data Sig (0,000) < 0.05.